Research progress of stimulus-responsive antibacterial materials for bone infection - Wang, Changqing; Xu, Peng; Li, Xiaoxu; Zheng, Yuhao; Song, Zhiming (Frontiers in Bioengineering and Biotechnology, 2022)
Infection is one of the most serious complications harmful to human health, which brings a huge burden to human health. Bone infection is one of the most common and serious complications of fracture and orthopaedic surgery. Antibacterial treatment is the premise of bone defect healing. Among all the antibacterial strategies, irritant antibacterial materials have unique advantages and the ability of targeted therapy. In this review, we focus on the research progress of irritating materials, the development of antibacterial materials and their advantages and disadvantages potential applications in bone infection.